Exploring EFL Learners’ Perceptions of Extensive Reading in Developing Writing Proficiency - Ali, Zulfiqar; Palpanadan, Sarala Thulasi; Asad, Mohammad Mujtaba (Development in Language Studies, 2023)
This study explored English as Foreign Language Learners’ (EFL) perceptions of extensive reading in developing their writing proficiency. The data were collected through semi-structured interviews and students’ reflective diaries from five participants based on a purposive sampling technique. The thematic analysis and personal interpretations techniques were used for the data analysis. The findings revealed that EFL learners perceived the ER approach as a useful method for developing their writing abilities. The learners also enjoyed participating in post-extensive reading writing activities. The study recommends that teachers should engage students in extensive reading along with post-reading writing activities. More research is suggested through multiple data collection tools in various educational contexts about the role of ER in developing the writing proficiency of learners.